Costochondral Grafting in Craniofacial Microsomia. Issue 2 (February 2015) - Tahiri, Youssef; Chang, Catherine S.; Tuin, Jorien; Paliga, J. Thomas; Lowe, Kristen M.; Taylor, Jesse A.; Bartlett, Scott P.
<x xml:space="preserve">Abstract</x> Background: Craniofacial microsomia encompasses a spectrum of diagnoses associated with variable degrees of mandibular hypoplasia, facial asymmetry, chin deviation, occlusal abnormalities, and potential airway compromise. This study presents one surgeon's experience with costochondral rib grafting for mandibular reconstruction in children with Pruzansky/Kaban type 2B and type 3 mandibular hypoplasia. Methods: An institutional review board–approved retrospective chart review was performed of all patients with craniofacial microsomia who underwent costochondral rib grafting for mandibular reconstruction performed by the senior author (S.P.B.) at The Children's Hospital of Philadelphia from January of 1998 to September of 2013. Demographic information, surgical history, operative details, postoperative complications, and outcomes were recorded. Plain radiographs and preoperative and postoperative three-dimensional computed tomographic scans were reviewed. Results: Two hundred fifty-five patients were diagnosed with craniofacial microsomia, and 22 patients met inclusion criteria. Twelve boys and 10 girls underwent grafting at an average age of 7.2 years. Thirty-three costochondral rib grafts were performed, 11 unilateral reconstructions and 11 bilateral reconstructions. Twelve hemimandibles were type 2B and 21 were type 3. No intraoperative complications were reported, and no incidence of graft resorption was noted. No additional procedures were required in 27 reconstructed hemimandibles (81.8 percent), whereas six (18.2 percent) required secondary distraction osteogenesis. Only one patient developed postoperative ankylosis. No malunion or nonunion was noted. Conclusion: The approach described in this article allowed the authors to obtain reliably good results with costochondral rib grafting for type 2B and type 3 mandibular hypoplasia associated with craniofacial microsomia. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.